ANALYSIS OF USABILITY ASPECTS USING ISO 25010 ON THE QUALITY OF THE SOFTWARE DIRECTIONS MOBILE APPLICATION - FATMAWATI SABUR; MUHAMMAD YAHYA; PURNAMAWATI PURNAMAWATI; MULYADI NUR (Jurnal Vokasi Keteknikan, 2023)
This research aims to determine the results of measuring product quality in the form of AMPA software (Mobile Directional Application) for the location of terminal service facilities at Sultan Hasanuddin Makassar International Airport. The subject of this research is AMPA software . The research procedure used is by adapting the Research and Development (R&D) development model with the ADDIE method with 5 (five) stages, namely: Analysis, Design, Development, Implementation, and Evaluation . The data source is quantitative data (questionnaire) which was tested using 100 respondents. The instrument used in data collection was a questionnaire instrument using a Likert scale. The data collection technique was carried out by observation and questionnaires. The data analysis technique used is descriptive analysis with reference to quantitative data obtained using the IBM SPSS statistical software program for Windows . The research results from the ISO 25010 test results on the usability aspect with 4 dimensions obtained an overall score in the quite decent category of 67.75%, the remainder in the less than feasible category of 15% and